2016
DOI: 10.4317/medoral.21077
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the analgesic efficacy of oral ketorolac versus intramuscular tramadol after third molar surgery: A parallel, double-blind, randomized, placebo-controlled clinical trial

Abstract: BackgroundPreemptive analgesia is considered an alternative for treating the postsurgical pain of third molar removal. The aim of this study was to evaluate the preemptive analgesic efficacy of oral ketorolac versus intramuscular tramadol after a mandibular third molar surgery.Material and MethodsA parallel, double-blind, randomized, placebo-controlled clinical trial was carried out. Thirty patients were randomized into two treatment groups using a series of random numbers: Group A, oral ketorolac 10 mg plus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 27 publications
0
26
0
2
Order By: Relevance
“…Oral Etirocoxib [10,22], celecoxib [11], acetaminophen [11], dexamethasone [17,21,24,25,35,36,39], diclofenac [17,36], codeine [17], ketorolac [19,21,43], methylprednisolone [25,35], paracetamol [26,48], dexketoprofen [26], ibuprofen [39,47,48], tramadol [40], nimesulide [40], ketoprofen [44], diflunisal [46], lornaxicam [46], rofecoxib [47].…”
Section: Nomentioning
confidence: 99%
“…Oral Etirocoxib [10,22], celecoxib [11], acetaminophen [11], dexamethasone [17,21,24,25,35,36,39], diclofenac [17,36], codeine [17], ketorolac [19,21,43], methylprednisolone [25,35], paracetamol [26,48], dexketoprofen [26], ibuprofen [39,47,48], tramadol [40], nimesulide [40], ketoprofen [44], diflunisal [46], lornaxicam [46], rofecoxib [47].…”
Section: Nomentioning
confidence: 99%
“…14 e Isiordia-Espinoza y cols. 6 mencionan que modula los receptores opioides y estimula la liberación de óxido nítrico. El ketorolaco es un inhibidor preferencial de la ciclooxigenasa 1 (COX-1), que se expresa constitutivamente y participa en la homeostasis de los procesos fisiológicos; sin embargo, también está presente durante el inicio del dolor posterior a cirugía de tercer molar 15 .…”
Section: Discussionunclassified
“…El diclofenaco es un AINE que por sus características farmacocinéticas y farmacodinámicas controla adecuadamente la tumefacción facial y el dolor postquirúrgicos 3 . El ketorolaco es otro AINE que ha evidenciado un adecuado efecto analgésico durante las primeras horas del postquirúrgico inmediato 6 .…”
Section: Introductionunclassified
“…But the choice of a synthetic molecule with a similar analgesic power to codeine was a determining factor for therapeutic success. Several authors 15,21,22 reported that pre-operative administration of analgesics reduce pain conditions in the immediate post-op, and suggest that preventive analgesia is an alternative for acute postoperative pain control in third molar extractions 23 . The preventive approach is started even before a painful stimulus is generated, thus preventing or even decreasing subsequent pain and the onset of CNS alterations during the surgical act [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Several authors 15,21,22 reported that pre-operative administration of analgesics reduce pain conditions in the immediate post-op, and suggest that preventive analgesia is an alternative for acute postoperative pain control in third molar extractions 23 . The preventive approach is started even before a painful stimulus is generated, thus preventing or even decreasing subsequent pain and the onset of CNS alterations during the surgical act [21][22][23][24] . In this line of reasoning, a preventive approach would be to start treatment with the association of HV (70mg) and paracetamol (750mg) 1 hour prior to surgery, to allow better bioavailability of the drug and therefore better postoperative analgesia, considering that both drugs act in synergy and promote comfort to the patient, without running the risk of genetic polymorphism.…”
Section: Discussionmentioning
confidence: 99%